Improving Performance on Preventive Health Quality Measures Using Clinical Decision Support to Capture Care Done Elsewhere and Patient Exceptions. (May 2018) - Bowen, Michael E.; Bhat, Deepa; Fish, Jason; Moran, Brett; Howell-Stampley, Temple; Kirk, Lynne; Persell, Stephen D.; Halm, Ethan A.
Preventive services required for performance measurement often are completed in outside health systems and not captured in electronic medical records (EMRs). A before–after study was conducted to examine the ability of clinical decision support (CDS) to improve performance on preventive quality measures, capture clinician-reported services completed elsewhere, and patient/medical exceptions and to describe their impact on quality measurement. CDS improved performance on colorectal cancer screening, osteoporosis screening, and pneumococcal vaccination measures ( P < .05) but not breast or cervical cancer screening. CDS captured clinician-reported services completed elsewhere (2% to 10%) and patient/medical exceptions (<3%). Compared to measures using only within-system data, including services completed elsewhere in the numerator improved performance: pneumococcal vaccine (73% vs 82%); breast (69% vs 75%), colorectal (58% vs 70%), and cervical cancer (53% vs 62%); and osteoporosis (72% vs 75%) screening ( P < .05). Visit-based CDS can capture clinician-reported preventive services, and accounting for services completed elsewhere improves performance on quality measures.